Association analysis between thrombospondin-2 gene polymorphisms and intervertebral disc degeneration in a Chinese Han population. Issue 2 (January 2018) - Yuan, Baisheng; Ji, Wei; Fan, Bing; Zhang, Binglei; Zhao, Yulin; Li, Jianmin
Abstract : Abstract: The aim of this study is to determine the contribution of 2 single nucleotide polymorphisms (SNPs) in thrombospondin 2 (THBS2) gene to the development of intervertebral disc degeneration (IDD) in a Chinese Han population. We studied 138 patients with radiographically proven IDD and 136 healthy volunteers with no history of back problems. Magnetic resonance images (MRIs) were obtained for all the patients and controls. Image evaluation for IDD was performed to evaluate the severity of IDD. All patients and controls were genotyped for rs6422747 and rs6422748. Associations between genotypes and development of IDD were analyzed. We found that 2 SNPs in the intron region of THBS2 gene (rs6422747 and rs6422748) were associated with susceptibility of IDD. However, they were not related with severity of IDD, including the total number of degenerative disc and level of IDD. G allele in both SNPs was associated with a higher risk of IDD. The 2 SNPs (rs6422747 and rs6422748) in the THBS2 gene were associated with susceptibility of IDD but not severity of IDD in a Chinese Han population. Our results indicated that THBS2 gene polymorphisms might be the risk factors for IDD. More studies with larger sample size need to be perfected to make sure the functions of THBS2 gene polymorphisms in IDD development.